3D Model of Bone Scaffolds Based on the Mechanical Behaviour for a Hybrid Nano Bio-composites / Jenan, S. Kashan and Saad M. Ali - Jenan, S. Kashan; M. Ali, Saad (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
Ceramic/polymer Nano composites in the view of possessing design uniqueness and property combinations have gained a great attention and reported to be the materials of the 21st century that are not found in conventional composites. In the present work, an attempt has been made to study, develop and improve the bio-mechanic for a designed and fabricated Ceramic/polymer bio-composite for a human natural bone repair and replacement in the case of complex fracture and bone diseases by adding the Nano fillers ceramic particles to the Polymer Matrix Nano composites (PMNC) for fabricated a hybrid Titanium dioxide and yttria stabilized zirconia reinforced high density polyethylene (HDPE) matrix bio-composites properties. These bioactive composites have been investigated by using hot pressing technique at different compression pressures of (30, 60, and 90 MPa) at a compounding temperature of (180, 190, and 200 °C). The SOLIDWORKS 17.0 and the finite element ANSYS 15.7 software programs were used to the simulation, modelling and analysing of femur bone biomechanics that can withstand the highest stresses and strains. The response surface methodology (RSM) technique was used to improve and verify the results. For all the fabricated Nano bio-composites systems, the results showed that the obtained output parameters values were increased with increasing the process input parameters, also the vice versa for the strain energy and equivalent elastic strain values, also the Nano ceramic compositions represented the main factor influenced the results. The main investigates results of the current research deduced that for the increase of the Nano ceramic powder (TiO2) contain from 1% to 10%, the compression fracture strength and the micro-Vickers hardness values increased by 50% and by 8.45%, respectively, and when adding 2% of zirconia (ZrO2), an additional increase in the compression fracture strength and micro hardness by 28.21% and 40.19% achieved, respectively. When using 10% TiO2 + 2% ZrO2/HDPE bio-composite at highest compact temperature of 200 °C and compounding pressure of 90 MPa, the strain energy and the equivalent elastic strain reduced by 82.69% and 14.53% when compared with using of 1% TiO2 content. While when increasing the nano ceramic content from 1% to 10% without adding the ZrO2 nano filler, they reduced by 142.25% and 67.81%, respectively. The maximum equivalent von Misses stress obtained is equal to 39.957MPa and when increasing the nano ceramic content from 1% to 10%, the stress safety factors and fatigue live values increased by 58.38% and by 46.28%, respectively and when adding 2% of zirconia (ZrO2), the stress safety factor reached its maximum values, with an additional increase in its values by 21.42% and 69.40%, respectively. These results give great choices to use successful in vivo tests and for a better life performance with any age, patient status and degree of injury.